2019
DOI: 10.1139/apnm-2018-0729
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid-induced perilipin 5 expression and lipid droplets formation are regulated by the PI3K/PPARα pathway in HepG2 cells

Abstract: Perilipin 5 (Plin5), a member of the PAT (Perilipin, ADRP, and Tip47) protein family, has been implicated in the regulation of cellular neutral lipid accumulation in nonalcoholic fatty liver diseases. However, the underlying regulatory mechanisms of Plin5 are not clear. The goal of the present study was to explore the mechanism of oleic acid (OA)-induced Plin5 expression in HepG2 cells. We found that the expression of Plin5 was increased during OA-induced lipid droplets formation in a dose- and time-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…The detailed mechanism of the antioxidant role of Plin5 via regulating Nrf2-ARE system in β-cells was explored preliminary in the present study. In some tissues, Plin5 has been reported to involve in the regulation of PI3K/Akt or MAPK pathways (p38 MAPK, ERK, and JNK) (21,24,40,44,49), which is the upstream modulators of Nrf2 in pancreatic β-cells (39,41). As evidenced by prior studies, excess ROS production and oxidative stress results in the activation of apoptotic p38 MAPK and JNK signaling, whereas activation of antiapoptotic PI3K/Akt and ERK pathways facilitates the translocation of Nrf2 into the nucleus, thereby activating the Nrf2/ARE pathway and alleviating oxidative damage (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The detailed mechanism of the antioxidant role of Plin5 via regulating Nrf2-ARE system in β-cells was explored preliminary in the present study. In some tissues, Plin5 has been reported to involve in the regulation of PI3K/Akt or MAPK pathways (p38 MAPK, ERK, and JNK) (21,24,40,44,49), which is the upstream modulators of Nrf2 in pancreatic β-cells (39,41). As evidenced by prior studies, excess ROS production and oxidative stress results in the activation of apoptotic p38 MAPK and JNK signaling, whereas activation of antiapoptotic PI3K/Akt and ERK pathways facilitates the translocation of Nrf2 into the nucleus, thereby activating the Nrf2/ARE pathway and alleviating oxidative damage (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that LD formation after stimulation with oleic acid (OA) leads to activation of PLIN5 in human liver cancer HepG2 cells via the PI3K/PPARα pathway [64].…”
Section: The Role Of Plin5 In Lipid Metabolism and Nafldmentioning
confidence: 99%
“…Recently, it was reported that LD formation after stimulation with oleic acid (OA) leads to activation of PLIN5 in human liver cancer HepG2 cells via the PI3K/PPARα pathway [ 64 ]. In the respective study, it was demonstrated that the PPAR inhibitor GW6471 decreased the levels of PLIN5 in a dose-dependent manner.…”
Section: The Role Of Plin5 In Lipid Metabolism and Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K/AKT is a classical pathway involved in insulin resistance, cell growth, and lipid metabolism associated with the inhibition of cholesterol efflux leading to LD formation [229]. In this sense, the participation of the PIK3 signaling pathway in MT-III-induced LDs in macrophages and vascular smooth muscle cells stimulated with MT-III has been demonstrated [167,224].…”
Section: Bothrops Svpla 2s Trigger Lipid Accumulation In Immunocompetent Cellsmentioning
confidence: 99%